STEM Distance Teaching: Investigating STEM Teachers' Attitudes, Barriers, and Training Needs - Katerina Tzafilkou; Maria Perifanou; Anastasios A. Economides (MDPI AG, 2022)
The aim of this study was to investigate STEM teachers' attitude towards STEM Distance Teaching (DT), as well as their perceived barriers and training needs. A mixed survey was conducted on 158 STEM teachers in secondary education who taught their courses fully online due to COVID-19. The results revealed that STEM teachers perceive STEM DT quite positively, but their attitude can be affected by several factors, such as the efficiency of the schools' digital infrastructure, as well as their gender, age, and STEM teaching subject. The qualitative thematic analysis identified several barriers to efficiently applying STEM DT, including the (i) lack of students' interaction and engagement, (ii) inefficiency of digital infrastructure, (iii) lack of students' and teachers' digital skills, (iv) lack of space/equipment, and (v) increased teaching workload. The generated themes of training needs highlighted the need for targeted and adjusted training to every STEM discipline, as well as training on DT tools and pedagogies. Finally, the results indicated the STEM teachers' need for psychological support and consulting.